2024
DOI: 10.1038/s41588-024-01665-2
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome evolution screens recapitulate tissue-specific tumor aneuploidy patterns

Emma V. Watson,
Jake June-Koo Lee,
Doga C. Gulhan
et al.

Abstract: Whole chromosome and arm-level copy number alterations occur at high frequencies in tumors, but their selective advantages, if any, are poorly understood. Here, utilizing unbiased whole chromosome genetic screens combined with in vitro evolution to generate arm- and subarm-level events, we iteratively selected the fittest karyotypes from aneuploidized human renal and mammary epithelial cells. Proliferation-based karyotype selection in these epithelial lines modeled tissue-specific tumor aneuploidy patterns in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Recent research has suggested that chromosomal imbalance inherent in aneuploidy can propel tumour heterogeneity and adaptability without the direct influence of specific driver gene mutations 37 . Complementing this perspective, further experiments of unbiased aneuploidy screens in normal human epithelial cells have identified a repeated selection of CNAs linked to cancer in a tissue-specific manner, in the absence of classic driver mutations 38 . The contrast between the direct impact of mutations and the more systemic influence of aneuploidy highlights the complexity of cancer evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested that chromosomal imbalance inherent in aneuploidy can propel tumour heterogeneity and adaptability without the direct influence of specific driver gene mutations 37 . Complementing this perspective, further experiments of unbiased aneuploidy screens in normal human epithelial cells have identified a repeated selection of CNAs linked to cancer in a tissue-specific manner, in the absence of classic driver mutations 38 . The contrast between the direct impact of mutations and the more systemic influence of aneuploidy highlights the complexity of cancer evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Three CNA-PCs reflecting large-scale gains were robustly associated with reduced NMD activity, most strongly CNA-PC3 and 86 located in regions 1q and 1q21-23.1. The 1q gain is found in ∼25% of cancers and it has been proposed to be selected through increasing dosage of the MDM4 oncogene phenocopying TP53 mutation 63 , or of MCL-1 antiapoptotic factor 96 or via upregulation of Notch genes 97 . This chromosome arm however also contains NMD factors SMG5 , SMG7 , the EJC gene RBM8A , and NMD-related genes INTS3 and SF3B4 , which we identified as associating with NMD efficiency upon CNA gain; additionally we identified 6 other genes involved in various RNA metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of NCSTN , present on 1q, positively correlated with Notch activation. 82 Together, these two studies suggest that 1q could be gained for multiple independent reasons. The proliferative advantage of chromosome 8 trisomy in the context of the oncogenic EWS-FLI1 fusion gene could be partially attributed to the copy number gain of the gene for the cohesin subunit RAD21 .…”
Section: What Is the Genetic Basis Behind Aneuploidy Patterns?mentioning
confidence: 96%